Оборонительная система Восточного укрепления Бельского городища - Шрамко, И.Б.; Корост, И.И.; Задников, С.А. (Археологія і давня історія України, 2018)
В статье обобщены все основные материалы по
изучению оборонительных сооружений Восточного
укрепления Бельского городища, подведены итоги
многолетних исследований, намечены направления
в дальнейшем изучении, охране и музеефикации памятника. At the present stage of the study of the famous Bilsk
hill fortress, it is important to analyze the information
gathered in extensive scientific literature reflecting
the development of scientific views on the designation
and organization of the defense system of one of
its most important component parts, followed by the
name «Eastern Fortification» in historiography. Consideration
of various points of view of scientists and
their arguments in defense of certain versions of the
time of construction, the nature of use, the principles
of construction and location in the general defense system of the Bilsk fortified settlement makes it possible
to conclude that there are still many unresolved issues in this problem. In this regard, new directions for
strengthening research are proposed, combining scientific tasks with protection measures and the inclusion
of a defensive shaft in the program of the museumification of a well-known monument of archeology.